2023
DOI: 10.1177/02761467231169880
|View full text |Cite
|
Sign up to set email alerts
|

WEIRD is not Enough: Sustainability Insights from Non-WEIRD Countries

Abstract: Henrich, Heine, and Norezayan (2010) published ‘The weirdest people in the world?’ in Behavoral and Brain Sciences (as of March, 2023 it has been cited 11 800 plus times in scholar.google). The paper introduced the concept of Western, Educated, Industrialised, Rich and Developed (WEIRD) countries/cultures and research subjects. It makes a cogent case for research based on those samples being unrepresentative of, and not useful to inform policy/behavior change/etc. of non-WEIRD countries. With this paper Henric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Also, the data were collected in Germany, one of the so-called WEIRD countries (western educated industrialized, rich, and democratic) [33] . Generalizability to other contexts with lower vaccine uptake, higher systematic barriers toward vaccination, or lower general trust in authorities and institutions is therefore limited [34] and replicational studies in different contexts are recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the data were collected in Germany, one of the so-called WEIRD countries (western educated industrialized, rich, and democratic) [33] . Generalizability to other contexts with lower vaccine uptake, higher systematic barriers toward vaccination, or lower general trust in authorities and institutions is therefore limited [34] and replicational studies in different contexts are recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, research findings are likely to be less generalisable to other countries and cultures (Apicella et al, 2020). Furthermore, a recent paper summarised sustainability insights from Non-Weird countries (Wooliscroft & Ko, 2023). Their findings indicated that applying "WEIRD" solutions to other countries is likely to be unsuccessful, as the factors that drive sustainable consumption are specific to the cultural context.…”
Section: Background Literaturementioning
confidence: 99%
“…Previous research cannot fully depict boundary-making scenarios, where majority and minority groups are considered insiders (locals) in a multicultural society. Responding to the growing focus on non-Western, educated, industrialised, rich and developed (WEIRD) countries and Wooliscroft and Ko's (2023) appeal for more non-WEIRD perspectives, this paper examines multicultural Malaysia, with a specific focus on the locally integrated minority group, the Malaysian Chinese.…”
Section: Introductionmentioning
confidence: 99%